Desempenho de um precipitador eletrostático operando na remoção de nanopartículas de aerossóis - Meira, Camila Roberta de (2009)
The removal of ultrafine particles is becoming an increasingly important operation due to the occupational problems caused to the environment and to the human health, such as inhalation of particulate matter, as well as by its applications in industrial processes. Among the equipments commonly employed for the removal of particulates from aerosols, the electrostatic precipitator (ESP) is the one capable to remove particles in a large size range with high efficiencies and can be used in the recovery of products of high aggregated value. The aim of this work was to evaluate the influence of operational parameters in the collection efficiency of a plate-wire electrostatic precipitator operating in the removal of nano-sized particles. The experimental system simulated a contamination by polydispersed nanoparticles ranging from 6 to 245 nm in an extra pure air stream. The efficiency for nano-sized particles was obtained by counting of particles before and after the electrostatic precipitator, using an electrical mobility analyzer. This procedure was performed varying the potential is applied to the discharge electrodes. The results shows the ESP presented a high efficiency of removal for nanoparticles of aerosol, where efficiencies larger than 99% were obtained for all velocities studieds (1 to 10 cm/s, with intervals of 1 in 1 cm/s) for electric field from 4 to 5.5 kV/cm. The efficiency increased with the decrease of the diameter particles up to approximately 20 nm, probably due to the higher electrical mobility of smaller particles. For diameters below 20 nm there was a drop in collection efficiency, which may have been caused by the low particles charging. The classical Deutsch-Anderson model didn t adjustment to the experimental data, the theoretical efficiency overestimated the experimental efficiency.